Priestia veravalensis sp. nov., isolated from coastal sample - Wagh, Vasudev S.; Ram, Hari; Dastager, Syed G. (Archives of Microbiology, 2021)
The taxonomic position of two isolates, SGD-V-76(T) and SGD-M-37, isolated from sediment sample of Veraval coast, India, was examined using the polyphasic taxonomic approach. The morphological and chemotaxonomic characteristics of these two organisms are typical of the genus Priestia. The phylogenetic analyses performed using almost complete 16S rRNA gene sequences demonstrated that the isolate belongs to the Bacillaceae family, and forms a clade within the cluster containing Priestia flexus MTCC 2909(T), Priestia aryabhattai B8W22(T) and Priestia megaterium KCTC 3007(T) and both strains showed highest similarity of > 98% with 3-29 nucleotide differences. The cell wall contained meso-diaminopimelic acid as the diagnostic diamino acid. The predominant isoprenoid quinone was MK-7 and the G + C content of strains was 37.5-37.7 mol%. However, the DNA-DNA hybridization and the phenotypic characteristics revealed that, the strain SGD-V-76(T) and strain SGD-M-37 are similar species but different from any known Priestia species with ANI values of 79.2, 79.3 and 79.2 and the dDDH values of 17.7, 17.8 and 18.0% respectively. On the basis of phenotypic characteristics, phylogenetic analysis and the results of biochemical and physiological tests, and genomic data strain SGD-V-76(T) was clearly distinguished from closely related members of the Priestia genus. Based on the above data analysis strain SGD-V-76(T) (= DSM28242(T) = KCTC33802(T) = CIP111056(T) = NCIM5510(T)) represents a novel species of the genus Priestia, and we propose the name Priestia veravalensis sp. nov.
Keywords: Coastal sediment; genome; Priestia; Veraval

Insights on biorational potential of Ocimum gratissimum essential oil and its binary combination with monoterpene phenol for control of rice weevil (Sitophilus oryzae) and aflatoxigenic fungi. - Remesh, V. Archana; Raveendran, Ashika; Bincy, K.; Wagh, Vasudev S.; Dastager, Syed G.; Babu, C. S. Vivek (Food Bioscience, 2022)
Food grain storage is a difficult task due to insect infestation and subsequent mycotoxin contaminations which adversely affects the nutritional quality of grains and leading to economic loss. Current research focuses on contact and fumigant toxicity effects of essential oils (EO) and aroma compounds against Sitophilus oryzae and growth inhibition of aflatoxigenic fungi. The EO of Ocimum gratissimum comprised of thymol (46.8%), gamma-terpi-nene (14.04%) along with o-cymene (11.76%). Also, Cymbopogon flexuosus rich in citral (76.3%) and geraniol (84.6%) and Cymbopogon nardus having geraniol (49.24%) and geranyl acetate (20.9%) were all evaluated using a dose of 25 mu L (Conc-833.3 mu L/L air) against S. oryzae. All the compounds showed significant mortality (>95%) at 24 h of exposure. The insecticidal property of O. gratissimum oil chemotype showed a strong contact and fumigant toxicity against S. oryzae at a highest dose of 25 mu L (Conc-833.3 mu L/L air) within 24 h. It has been further evaluated on three aflatoxigenic fungal strains which showed reduction in growth and aflatoxin content (Aflatoxin B and G), which was markedly reduced upon the treatment. The binary mixture interaction of O. gratissimum oil with monoterpene phenol (carvacrol) was assessed and the specific binary mixture of 80:20 ratio (having additive property) acts as a contact insecticide with 100% mortality. Hence, essential oil of less explored Ocimum species (O. gratissimum) and its binary mixture could be deployed as potential biorational for control of rice weevil (Sitophilus oryzae) and aflatoxigenic Aspergillus spp.
Keywords: Aflatoxigenic fungi; Binary combination; Essential oil; Ocimum gratissimum; Sitophilus oryzae

Isolation and structural characterization of exopolysaccharide from marine Bacillus sp. and its optimization by Microbioreactor - Wagh, Vasudev S.; Said, Madhukar S.; Bennale, Jagadish S.; Dastager, Syed G. (Carbohydrate Polymers, 2022)
In the present study, a cost-effective, robust Microbioreactor based production optimization of levan like exopolysaccharide from marine Bacillus sp. SGD-03 was analysed. FE-SEM analysis has showed the significant fibrillar structure of EPS. Size exclusion chromatography and other analytical data revealed that, produced EPS has a molecular weight of 1.0 x 10(4) Da and is composed of fructose monosaccharide with hydroxyl, carbonyl, and ether groups. The backbone structure of EPS has a branching pattern of beta-(2,6) linkages which confirms the similarity with available levan like polymers. The cost-effective media composition for levan production was demonstrated. The maximum yield of crude levan obtained was 123.9 g/L by response surface methodology using robust BioLector Pro Microbioreactor, and same has been validated with shake flask, 1 L and 10 L pilot-scale fermentation.
Keywords: EPS; marine; Microbioreactor; Optimization; structure

Vat-based 3D-bioprinted scaffolds from photocurable bacterial levan for osteogenesis and immunomodulation - Waidi, Yusuf Olatunji; Wagh, Vasudev S.; Mishra, Shivangi; Jhunjhunwala, Siddharth; Dastager, Syed G.; Chatterjee, Kaushik (Biomacromolecules, 2025)
Emerging techniques of additive manufacturing, such as vat-based three-dimensional (3D) bioprinting, offer novel routes to prepare personalized scaffolds of complex geometries. However, there is a need to develop bioinks suitable for clinical translation. This study explored the potential of bacterial-sourced methacrylate levan (LeMA) as a bioink for the digital light processing (DLP) 3D bioprinting of bone tissue scaffolds. LeMA was successfully synthesized, characterized, and used to fabricate 3D-bioprinted scaffolds with excellent printability and physicochemical properties. In vitro studies demonstrated superior cytocompatibility of 15% w/v LeMA gels compared to 20% gels. 15% LeMA gels supported osteogenic differentiation , as evidenced by alkaline phosphatase activity and mineral deposition by MC3T3 pre-osteoblasts. Importantly, the LeMA hydrogels positively modulated the macrophage phenotype, promoting the expression of the anti-inflammatory marker CD206. These findings suggest that 3D-printed LeMA scaffolds can create a favorable microenvironment for bone regeneration, highlighting their potential for tissue repair and regeneration applications.